2018
DOI: 10.1177/1071100718786494
|View full text |Cite
|
Sign up to set email alerts
|

Functional Outcomes of Local Pedicle Graft Interpositional Arthroplasty in Adults With Severe Freiberg’s Disease

Abstract: Level IV, retrospective case series.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 26 publications
(40 reference statements)
0
6
0
Order By: Relevance
“…6 A case report also suggested using palmaris longus autograft as an interpositional allograft with a satisfactory outcome. 12 Recently, Abdul et al 1 described the use of a local pedicle graft as an interposition, called a “Rollmop,” for severe Freiberg disease. They studied 25 patients and found a significant decrease in VAS pain scores and an increase in American Orthopaedic Foot & Ankle Society ankle-hindfoot scale scores.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…6 A case report also suggested using palmaris longus autograft as an interpositional allograft with a satisfactory outcome. 12 Recently, Abdul et al 1 described the use of a local pedicle graft as an interposition, called a “Rollmop,” for severe Freiberg disease. They studied 25 patients and found a significant decrease in VAS pain scores and an increase in American Orthopaedic Foot & Ankle Society ankle-hindfoot scale scores.…”
Section: Discussionmentioning
confidence: 99%
“…Other authors have described, in small series or case reports, procedures using a variety of soft tissues and synthetic materials for interpositional arthroplasties including dorsal capsule, 9 extensor digitorum brevis, 14 extensor digitorum longus, 6 palmaris longus autograft, 12 and silicone. 2 Recently, Abdul et al 1 described the use of a local pedicle graft as an interposition arthroplasty for severe Freiberg disease. Coughlin and Shurnas 4 described the use of a rolled allograft tendon as an interposition soft tissue arthroplasty for the treatment of advanced hallux rigidus with preparation of both sides of the first MTP joint to accept the spherical graft.…”
Section: Introductionmentioning
confidence: 99%
“…3 Several articles have reported good clinical outcomes of interposition arthroplasty using soft tissue such as the extensor digitorum longus, extensor digitorum brevis, palmaris longus, periosteum with a fat pedicle graft, and allograft of the semitendinosus tendon. [39][40][41][42][43][44] Çevik et al 44 reported the mid-to long-term results of interposition arthroplasty with the extensor digitorum brevis tendon. After a mean follow-up 133.8 (range, 60-198) months, the AOFAS scores improved as did the range of motion in dorsiflexion and plantar flexion.…”
Section: Joint-sacrificing Procedures Interposition Arthroplastiesmentioning
confidence: 99%
“… 3 Several articles have reported good clinical outcomes of interposition arthroplasty using soft tissue such as the extensor digitorum longus, extensor digitorum brevis, palmaris longus, periosteum with a fat pedicle graft, and allograft of the semitendinosus tendon. 39 - 44 …”
Section: Joint-sacrificing Proceduresmentioning
confidence: 99%
See 1 more Smart Citation